1980
DOI: 10.3758/bf03337092
|View full text |Cite
|
Sign up to set email alerts
|

Goal vs. alley punishment after escape training: Massed trials and startbox conditions

Abstract: Two different starting procedures, drop box vs . guillotine door, were used in giving 36 male rats 20 massed shock-escape trials in a straight runway. On subsequent trials, the animals encountered no shock at all, shock punishment in the middle 2 ft of the 4-ft alley, or shock for .5 sec immediately after entering the goalbox. The guillotine-door procedure produced faster running in extinction, alley punishment facilitated responding, and goal punishment suppressed responding. Results were interpreted in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The finding that rats shocked on 100% of extinction trials performed similarly to those not shocked at all during extinction was unexpected because all previous studies using goal-shock on 100% of extinction trials reported that such animals rapidly supressed responding compared to nonshocked animals (Babb et al, 1987;Matthews & Babb, 1985;Meeker et al, 1980). The only procedural difference between this study and prev ious ones was the use of Long-Evans rats in thecurrent study.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The finding that rats shocked on 100% of extinction trials performed similarly to those not shocked at all during extinction was unexpected because all previous studies using goal-shock on 100% of extinction trials reported that such animals rapidly supressed responding compared to nonshocked animals (Babb et al, 1987;Matthews & Babb, 1985;Meeker et al, 1980). The only procedural difference between this study and prev ious ones was the use of Long-Evans rats in thecurrent study.…”
Section: Discussionmentioning
confidence: 47%
“…Earlier research, using a spaced trials procedure and goal-shock on 100% of extinction trials, indicated that number of acquisition trials does affect extinction performance, with greater facilitation associated with larger numbers of acquisition trials . Moreover, it has been demonstrated with both spaced and massed trials that percentage of shocked extinction trials affects extinction performance, with higher percentages of goal-shocked trials leading to suppression when a massed trials procedure is used (Meeker, Babb, & Matthews , 1980) and to facilitation when a spaced trialsprocedure is used (Matthews & Babb , 1978). Low percentages of goal-shocked extinction trials lead to facilitation regardless of whether a massed or spaced trials procedure is utilized (Babb et al, 1987).…”
mentioning
confidence: 99%
“…Assuming the US aftereffects constitute a component of the aversive response to shock, rather than an opponent reaction (Solomon & Corbit, 1974), they may add to any aversive tendencies in the goalbox and they may do so to a greater degree the shorter the interval between trials. Considering these various possible influences, an experiment was designed to test the thesis that the goalbox of a straight runway becomes more aversive when shock-escape trials are massed as compared with spaced, with those terms designating procedures used in prior relevant studies (Babb & Hom, 1971;Meeker, Babb, & Matthews, 1980). After 20 massed or spaced shock-escape trials, animals were given 5 successive trials without shock but with one of three test conditions present in the goalbox.…”
mentioning
confidence: 99%